A Few of My Favourite Things: The Feiticeiro/a as Foundation for ‘Pervert’ Characterisation - Theo, LJ (Constructing Transgressive Sexuality in Screenwriting: The Feiticeiro/a as Character, 2017)
A non-foundationalist construct for the Feiticeiro/a character that assumes neither an essentialist nature nor a determinist set of activities is possible. This does not prescribe a ‘type’ of ‘pervert’ character, but instead delineates an epistemic framing for a Feiticeiro/a character. This chapter explores an etymologically based semiotic approach to character construction that accounts for a Derridean view that language is constituted by binary reciprocal delimitations and for a view of sex as a dereified expression of materialised instances of engagement by sexual subjects, in terms of which sexuality is rendered as an opened-outward and connected function. The chapter further deals with an approach based in an empathic engagement between audiences and Feiticeiro/a characters, which is apposite for audiences identifying with but not necessarily liking characters. The chapter closes the volume’s argument around how transgressive, sexually focused Feiticeiro/a characters might productively be constructed in terms other than of essences and determinist actions, but in terms of ‘meaning’ found in the points of connection between heterogeneous bodily surfaces.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé